Market segmentation (G + Customer and Product Profile Tools) for Gender Responsive Bean Breeding in Zimbabwe - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2024)
The study aims to enhance gender-responsive bean breeding in Zimbabwe using the G+ Customer and Product Profile Tools. It focuses on profiling customer preferences and product traits to address food security, nutrition, and gender gaps. The data covers major topics like market segmentation, customer mapping, socioeconomic characteristics, and bean traits. Key questions include gender-specific preferences, constraints in accessing improved varieties, and the role of beans in livelihoods and food securityThe study aims to enhance gender-responsive bean breeding in Zimbabwe using the G+ Customer and Product Profile Tools. It focuses on profiling customer preferences and product traits to address food security, nutrition, and gender gaps. The data covers major topics like market segmentation, customer mapping, socioeconomic characteristics, and bean traits. Key questions include gender-specific preferences, constraints in accessing improved varieties, and the role of beans in livelihoods and food security.